Neuromotricity as a new paradigm - Romero-Naranjo, F. J.; Andreu-Cabrera, E. (Journal of Human Sport & Exercise, 2023)
The review of the existing narrative shows the theoretical evolution of the concepts of motricity and psychomotricity, which have led to a new paradigm of movement called neuromotricity. In this new approach to motor action, cognitive functions, and especially executive functions, form part of its essence. This is why neuromotricity, as a discipline independent of psychomotricity, proposes a completely different set of activities in which the dual task is always present. The methodology of applied neuromotricity could promote the generation of neural networks through stimulation protocols of increasing complexity, which in turn improve brain functions.